2012
DOI: 10.1117/12.912089
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of the correlation between interest points and gaze points

Abstract: This study intends to measure the degree of correlation/similarity between the subjective gaze points (obtained by eye tracking experiments) and the objective interest points of several well-known detectors such as Harris and SURF. For each of the latter, we look for the best setting in term of maximization of likeness with the gaze points. For this task, the Earth Mover's Distance (EMD) 1 is used to compare two data-sets with different cardinalities. We also used ANOVA to measure the influence of each paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This choice can be justified by the ability of these interest points to capture and predict salient features (signal ruptures) on a given image. Moreover, the similarity between interest points (Harris, SIFT and SURF) and gaze points, for a given set of parameters, has been demonstrated by Nauge et al [9]. Therefore, our spatial saliency map is purely based on interest points, without accounting for the influence of central bias and top-down information.…”
Section: Spatial Dimensionmentioning
confidence: 90%
See 1 more Smart Citation
“…This choice can be justified by the ability of these interest points to capture and predict salient features (signal ruptures) on a given image. Moreover, the similarity between interest points (Harris, SIFT and SURF) and gaze points, for a given set of parameters, has been demonstrated by Nauge et al [9]. Therefore, our spatial saliency map is purely based on interest points, without accounting for the influence of central bias and top-down information.…”
Section: Spatial Dimensionmentioning
confidence: 90%
“…Lowe et al showed in his work that the properties of SIFT interest points are similar to those of neurones in the inferior temporal cortex [7]. Moreover, Nauge et al have shown that there is a correlation between interest points and gaze points [9] depending on the parameters tuning. Accordingly, it appears possible to rely on interest points for modeling visual attention.…”
Section: Introductionmentioning
confidence: 98%
“…They have been selected thanks to their capacity to predict a signal rupture on an image, that is often correspond to a salient feature. Furthermore, Nauge et al proved in their work [31] the resemblance between fixation points and interest points (Harris, SIFT and SURF) by tuning the settings of the latter. For our purposes, we extract the salient features using only the interest points, no center bias and top-down information has been considered.…”
Section: Spatial Featuresmentioning
confidence: 99%
“…A new direction for saliency evaluation has been opened by the notion of interest points, like Harris detector [16], SIFT (Scale-Invariant Features Transformation) [27] or SURF (Speeded Up Robust Features) [2]. Nauge et al in their work [31] with multiple tests showed the correlation between gaze and interest points thanks to their tuning parameters. The same authors proposed a saliency model for 2D still images based on the properties of interest points [30].…”
Section: Introductionmentioning
confidence: 99%